2020
DOI: 10.1007/s11886-020-01278-1
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in Acute Myocarditis: How Immunopathogenesis Steers New Directions for Diagnosis and Treatment

Abstract: Purpose of Review Over the last decade, myocarditis has been increasingly recognized as common cause of sudden cardiac death in young adults and heart failure overall. The purpose of this review is to discuss hypothesis of development of non-infectious myocarditis, to provide a description of the immunopathogenesis and the most common mechanisms of autoimmunity in myocarditis, and to provide an update on therapeutic options. Recent Findings A new entity of myocarditis is immune checkpoint inhibitor (ICI) induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 101 publications
0
21
0
3
Order By: Relevance
“…Myocarditis refers to as localized or diffuse inflammatory lesions of the myocardium, initiated by infectious factors, most commonly, viruses and non‐infectious factors, such as systemic autoimmune disease, medications and cardiotoxins 40 . It is believed that IL‐13 consecutively contributes to regulating recruitment and differentiation of immune cells, chemokines secretion and fibrosis during the progression of myocarditis 40‐42 .…”
Section: Role Of Il‐13 In Cvdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Myocarditis refers to as localized or diffuse inflammatory lesions of the myocardium, initiated by infectious factors, most commonly, viruses and non‐infectious factors, such as systemic autoimmune disease, medications and cardiotoxins 40 . It is believed that IL‐13 consecutively contributes to regulating recruitment and differentiation of immune cells, chemokines secretion and fibrosis during the progression of myocarditis 40‐42 .…”
Section: Role Of Il‐13 In Cvdsmentioning
confidence: 99%
“…Myocarditis refers to as localized or diffuse inflammatory lesions of the myocardium, initiated by infectious factors, most commonly, viruses and non‐infectious factors, such as systemic autoimmune disease, medications and cardiotoxins 40 . It is believed that IL‐13 consecutively contributes to regulating recruitment and differentiation of immune cells, chemokines secretion and fibrosis during the progression of myocarditis 40‐42 . IL‐13 deficiency mice develop into severe myocarditis in both coxsackievirus B3 (CVB3)‐induced model and experimental autoimmune myocarditis (EAM) model, manifested in decreased systolic and diastolic left ventricular functions and decreased survival 41 .…”
Section: Role Of Il‐13 In Cvdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fulminant myocarditis is defined as a myocarditis that leads within four weeks or less of symptom onset to severe heart failure, requiring medical and/or mechanical cardiovascular support. The most common etiology is viral or autoimmune in nature and, less commonly, hypersensitivity and toxic reactions to drugs [41], as well as giant cell myocarditis (a rare but very aggressive form of myocarditis often associated with autoimmune diseases).…”
Section: Myocarditismentioning
confidence: 99%
“…Although GD is a common autoimmune thyrotoxicosis and well-known to be related to chronic heart failure (especially dilated cardiomyopathy), hyperthyroidism-associated acute myocarditis is rarely reported. However, retrospective studies reported that 9–16% of unexplained non-ischemic dilated cardiomyopathy cases have a histological evidence of myocarditis ( 9 ). Thus, there may exist huge omissions about hyperthyroidism-related myocarditis in GD patients.…”
Section: Introductionmentioning
confidence: 99%